Role of 3 Tesla MR Fistulogram in Evaluation of Perianal Fistulas - Vaibhav, Takkalapally Prasanna; Madhusudana, Yarramsetti; Manam, Gayatri; K S Vedaraju (Asian Journal of Medical Radiological Research, 2022)
Background: An unusual association b/w two organs and structures in the body is called a fistula, it may be also formed between an organ & skin of the body. Perianal fistula is an infrequent but critical GIT condition that can cause substantial morbidity. It develops due to various reasons but usually as a result of anorectal abscess. Men have a higher prevalence than women. It is a connection due to septic ulceration/ I&D which formed surrounding rectum &anus, characterized by the development of improper connection b/w rectum & anal canal, to that of skin present over the anus. There are different classifications for perianal fistulas. The Parks classification is used widely for surgical classification and distinguishing 4 types. Radiologists have devised a new grading system for perianal fistulae called the St James’s University Hospital classification, which comprises five grades and is based on landmarks on the axial plane. It also includes abscesses and secondary extensions. Because they are based on anatomical features, they are simple to utilize. A perianal fistula can be evaluated using a variety of imaging techniques. X-ray fistulography, endoanal ultrasonography, CT fistulography, and MR fistulogram are some of the options. The MR Fistulogram is a required imaging modality for the identification of fistula in ano, and its multiplanar reconstruction has proven to be extremely useful in surgery for characterizing and classifying fistulas based on their relationship to the diaphragm of the pelvis and the anal sphincter. Subjects and Methods: Patients referred to the department of Radiodiagnosis at Narayana Medical College and Hospital in Nellore were the main source of data. There are 42 individuals in this hospital-based prospective research. This study was conducted over two years (i.e., from Jun 2019 to Jun 2021). The subjects who gave informed consent were studied on a 3 Tesla GE MRI Scanner (GE Discovery 750w). Results: Our research included 42 people who had clinical and investigative features that pointed to an anal fistula. With a male to female ratio of 3:2, the bulk of the patients were men. The majority of the people were in their 30s and 50s. Tuberculosis and Crohn’s disease were found to be co-morbidities. The intersphincteric form of fistula was the most common among the 42 patients in the study, followed by the trans sphincteric type. When the fistulous tracts were examined in our investigation, the majority of the patients had only one external opening. In most of the cases the opening was between 4 and 6 o’clock. When examining the internal opening, the majority of patients had only one. The internal opening was most commonly found in the 4 to 6 o’clock position. The surgical findings matched the study’s findings on the location of the openings. We used the St James’s University Hospital Classification to categorise perianal fistulas in our investigation. Grade I fistulas were found to be the most common, followed by grade III fistulas. Abscesses were seen in 8 of 42 patients (19.05%) and secondary tracts in 12 of 42 (28.57 percent). In our study, there is a significant correlation (p-value 0.006) between the fistulous tracts identified on the 3 Tesla MR Fistulogram and the surgical findings. Conclusion: Perianal fistula is a rare problem that can become chronic and recurrent. There are several complications, such as tracks and an abscess. Inadequate assessment of these consequences can lead to recurrent and persistent illness. As a result, a thorough examination of perianal fistulas is required prior to surgery. In order to avoid injury to the external sphincter and subsequent faecal incontinence, it is also necessary to establish the sphincter’s relationship with the fistulous pathways. The 3 Tesla MR Fistulogram meets all of these requirements for surgeons and aids in surgery. The 3 Tesla MR Fistulogram identifies secondary tracks and abscesses as well as providing detailed anatomic details of the fistula. It can also tell the difference between scar tissue and granulation tissue. We conclude that a 3 Tesla MR Fistulogram is the best way to assess anorectal fistulas prior to surgery.